(untitled) (Eurasian Journal of Ecology, 2021)
Anatomical parameters of the flag leaf as criteria for drought tolerance of two alloplasmic lines (interspecific hybrids) and their parental forms − T. aestivum L. (cultivar of Mironovskaya-808) and T. dicoccum wheat were presented. The parameters studied were the thickness of the abaxial and adaxial epidermis, the thickness of the mesophyll and central vein, and the diameter of the central conducting bundle of the flag leaf. Different degrees of negative impact of sudden drought-stress and permanent water deficit on the anatomical structure of the flag leaf were shown. At the stage of flag leaf formation, anatomical parameters, for example an increase or preservation of the size of the protective and mechanical leaf tissues and the thickness of the mesophyll under stress can serve as criteria for the selection of drought-resistant forms of wheat. It revealed that among the studied genetic lineages the alloline D-d-05 showed the best adaptability and the most stable anatomical parameters of the flag leaf under conditions of moisture deficiency. The different degrees of drought tolerance of the studied lines indicate that the combination of the nucleus and cytoplasm of the parental forms can contribute to both an increase and a decrease in the level of drought tolerance in interspecific hybrids, which indicates the need to continue research with additional molecular genetic analysis. Key words: wheat, allolines, flag-list, anatomy, drought tolerance.